Offering care for victims of torture among a migrant population in a transit country: a descriptive study in a dedicated clinic from January 2017 to June 2019. Issue 2 (6th October 2020) - Keshk, Manar; Harrison, Rebecca; Kizito, Walter; Psarra, Christina; Owiti, Phillip; Timire, Collins; Camacho, Mabel Morales; De Maio, Gianfranco; Safwat, Hadeel; Matboly, Abeer; Van den Bergh, Rafael
Abstract: Background: Medecins Sans Frontieres set up a clinic to provide multidisciplinary care to a vulnerable migrant population experiencing torture. We describe the population accessing care, the characteristics of care provided and patient outcomes. Methods: A descriptive retrospective cohort study of patients enrolled in care during January 2017–June 2019 was conducted. Results: Of 2512 victims of torture cases accessing the clinic, the male: female ratio was 1:1. About 67% of patients received medical care, mostly for chronic pain treatment. About 73% of patients received mental healthcare, 37% received physiotherapy and 33% received social support care; 49% came to the clinic upon the recommendation of a friend or family member. The discharge with improvement rate ranged from 23% in the mental health service to 9% in the sociolegal service. Patients retained in care had a median IQR of 3 (2–4) follow-up visits for medical care, 4 (2–7) for mental health, 6 (3–10) for physiotherapy and 2 (1–4) for sociolegal. Conclusion: Care for victims of torture cases among vulnerable migrants is complex. For those who did receive care that led to an improvement in their condition, their care models have been described, to allow its implementation in other non-specialised settings.